Social media in higher education: A look at participatory culture in graduate coursework - Davidson, Ann-Louise; Fountain, Renee-Marie (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2013)
Society has become fascinated with web-based social media. Recently, aspects of social media environments such as participatory culture, new media digital literacies, and connectivism have been increasingly investigated. However, current university policies often restrict, if not forbid, the use of social networking sites in class. For professors seeking to introduce social media into their teaching practice, these restrictive policies can make it difficult to teach with and about social computing and computer-supported collaborative work. This descriptive paper presents the experiences of two professors who integrated Web 2.0 practices into their respective graduate-level education courses titled Social Computing and Computer-Supported Collaborative Work and Web 2.0 = Pedagogy 2.0? and describes their underlying theories and concepts. Subsequently, the courses’ rationales theoretical underpinnings, and teaching approaches are delineated, and implementation strategies are suggested.